Assessing cross-national invariance of the Community Assessment of Psychic Experiences (CAPE). Issue 15 (5th December 2018) - Pignon, Baptiste; Peyre, Hugo; Ferchiou, Aziz; van Os, Jim; Rutten, Bart P. F.; Murray, Robin M.; Morgan, Craig; Leboyer, Marion; Schürhoff, Franck; Szöke, Andrei; ,
Abstract: Background: The Community Assessment of Psychic Experiences (CAPE) is a 42-item self-report questionnaire that has been developed and validated to measure the dimensions of psychosis in the general population. The CAPE has a three-factor structure with dimensions of positive, negative and depression. Assessing the cross-national equivalence of a questionnaire is an essential prerequisite before pooling data from different countries. In this study, our aim was to investigate the measurement invariance of the CAPE across different countries. Methods: Data were drawn from the European Union Gene-Environment Interaction (EU-GEI) study. Participants (incident cases of psychotic disorder, controls and siblings of cases) were recruited in Brazil, France, Italy, the Netherlands, Spain and UK. To analyse the measurement invariance across these samples, we tested configural invariance (i.e. identical structures of the factors), metric invariance (i.e. equivalence of the factor loadings) and scalar invariance (i.e. equivalence of the thresholds) of the three CAPE dimensions using multigroup categorical confirmatory factor analysis methods. Results: The configural invariance model fits well, providing evidence for identical factorial structure across countries. In comparison with the configural model invariance, the fit indices were very similar in the metric and scalar invariance models, indicating that factor loadings and thresholds did not differ across the six countries. Conclusion: We found that, across six countries, the CAPE showed equivalent factorial structure, factor loadings and thresholds. Thus, differences observed in scores between individuals from different countries should be considered as reflecting different levels of psychosis.